The Effect of Multiple Choice and Essay Assessments Based on Everyday Contexts on English Learning Outcomes of Students in Grade VII of Junior High School - Amalia Zulfan Hadi; Nasiha Amirotul Khoiriyah; Mika Avialisha Tama; Selnistia Hidayani (Jurnal Intelek Insan Cendikia, 2025)
This study investigates the implementation and outcomes of context-based multiple-choice and essay assessments in English learning among seventh-grade junior high school students as young learners. Using a descriptive quantitative method, 16 students at SMP Islam Nur Al Qalam were tested using questions related to daily life topics (e.g., self-introduction, daily routines). Results showed that 75% scored in the “Good” to “Excellent” range on the multiple-choice test, and 50% did so on the essay section. These findings suggest that contextual assessments enhance students’ understanding and expression, supporting the Contextual Teaching and Learning theory. The study concludes that this assessment approach is effective and appropriate for evaluating English outcomes in young learners. Therefore, contextual assessments are considered effective and age-appropriate tools for evaluating English learning outcomes among young learners in junior high school.